Providing noncontingent, alternative, functional reinforcers during delays following functional communication training. Issue 4 (19th April 2020) - Sumter, Meagan E.; Gifford, Margaret R.; Tiger, Jeffrey H.; Effertz, Hannah M.; Fulton, Caitlin J.
Abstract : Functional Communication Training (FCT) involves arranging extinction for problem behavior and reinforcement for a more desirable, functionally equivalent, communicative response (FCR). Although effective under ideal arrangements, the introduction of delays to reinforcement following the FCR can result in increased problem behavior. Austin and Tiger (2015) showed that for individuals whose problem behavior was sensitive to multiple sources of reinforcement, providing access to alternative, functional reinforcers during delays mitigated this increase in problem behavior during delay fading. The current study replicated the procedures of Austin and Tiger with 2 individuals displaying multiply controlled problem behavior. Providing alternative functional reinforcers reduced problem behavior during 10‐min delays for both participants without requiring delay fading.